Pengaruh Knowledge Sharing dan Kompetensi Terhadap Kinerja Pegawai Dimediasi Kepuasan Kerja: Studi Kasus pada Pegawai Balai Besar Pelatihan Vokasi dan Produktivitas Semarang - Budisari, Dinka; Lieana, Lie (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of knowledge sharing and competence on employee performance, mediated by job satisfaction. This study employed a quantitative approach with a sample of 145 employees from the Semarang Vocational Training and Productivity Center (BBPVP). Data were analyzed using SPSS version 26. The data analysis techniques included respondent descriptions, variable descriptions, validity tests, reliability tests, F-tests, R² tests, t-tests, and Sobel tests. The results indicate that knowledge sharing has no effect on job satisfaction; competence has a positive effect on job satisfaction; knowledge sharing has no effect on employee performance; competence has a positive effect on employee performance; job satisfaction has a positive effect on employee performance; job satisfaction does not mediate the effect of knowledge sharing on employee performance; and job satisfaction mediates the effect of competence on employee performance.